Efficacy of combined orthokeratology and 0.01% atropine solution for slowing axial elongation in children with myopia: a 2-year randomised trial - Kinoshita, Nozomi; Konno, Yasuhiro; Hamada, Naoki; Kanda, Yoshinobu; Shimmura-Tomita, Machiko; Kaburaki, Toshikatsu; Kakehashi, Akihiro (Scientific reports, 2020)
Eighty Japanese children, aged 8–12 years, with a spherical equivalent refraction (SER) of − 1.00 to − 6.00 dioptres (D) were randomly allocated into two groups to receive either a combination of orthokeratology (OK) and 0.01% atropine solution (combination group) or monotherapy with OK (monotherapy group). Seventy-three subjects completed the 2-year study. Over the 2 years, axial length increased by 0.29 ± 0.20 mm ( n = 38) and 0.40 ± 0.23 mm ( n = 35) in the combination and monotherapy groups, respectively ( P = 0.03). Interactions between combination treatment and age or SER did not reach significance level (age, P = 0.18; SER, P = 0.06). In the subgroup of subjects with an initial SER of − 1.00 to − 3.00 D, axial length increased by 0.30 ± 0.22 mm ( n = 27) and 0.48 ± 0.22 mm ( n = 23) in the combination and monotherapy groups, respectively ( P = 0.005). In the − 3.01 to − 6.00 D subgroup, axial length increased by 0.27 ± 0.15 mm ( n = 11) and 0.25 ± 0.17 mm ( n = 12) in the combination and monotherapy groups, respectively ( P = 0.74). The combination therapy may be effective for slowing axial elongation, especially in children with low initial myopia.